Sustainable and Flipped STEM Education: Formative Assessment Online Interface for Observing Pre-Service Teachers' Performance and Motivation - Jin Su Jeong; David González-Gómez; Félix Yllana Prieto (MDPI AG, 2020)
Sustainable science, technology, engineering, and mathematics (STEM) education involves lifelong education in various domains. Active learning strategies are receiving increased attention as an important tool, and particularly online-based formative assessment interfaces, although challenges to their use remain in sustainable and flipped STEM education. In this research, we observed pre-service teachers' (PSTs') performance and motivation in a university STEM course that was planned as a randomized examination of 71 students during a 2017/2018 course with an online interface for sustainable and flipped formative assessment. In terms of PSTs' standardized performance and the motivation effect survey, we gathered and examined the data to observe pre- and post-test results on adaptive assignments. Additionally, feedback from/to instructors and their log records were recorded by the proposed interface. The results demonstrate the PSTs' positive performance and motivation, and the feedback and log records reiterate its positive influence with 98.6% participation in the sustainable and flipped online formative assessment interface. Consequently, the foremost drawbacks and challenges that current and traditional STEM education are facing are meaningfully reflected by the results obtained. Thus, the platform allows PSTs to be more involved in experimental contexts and validates learning performance, and the motivations effect survey provides a sustainable and active learning methodology for their future profession.